Prolongiertes Weaning bei Patienten mit ARDS - Braune, Stephan; Schönhofer, Bernd (DMW - Deutsche Medizinische Wochenschrift, 2017)
The clinical course of moderate to severe ARDS often leads to prolonged weaning. Prolonged weaning utilizes considerable resources in intensive care medicine and is associated with a high mortality. The pathophysiology of prolonged weaning is complex and its understanding mandatory for its successful management. This article discusses and summarizes the most important causes of prolonged weaning and the corresponding treatment strategies to liberate patients with ARDS from the ventilator.
Keywords: ARDS; prolongiertes Weaning; FVIDD; ICU-AW; Sedierung; Frühmobilisierung